Formation of wells for underground engineering communications by a screw working body - Suponev, Vladimir; Rugulin, Vitaly (Transfer of innovative technologies, 2021)
A new method of creating soil cavities for trenchless laying of underground utilities with the help of a screw working body is proposed. The calculated dependences are obtained and the estimation for practical implementation is given.